2021
DOI: 10.1111/cts.12950
|View full text |Cite
|
Sign up to set email alerts
|

Outreach to new mothers through direct mail and email: recruitment in the Early Check research study

Abstract: Meeting recruitment targets for clinical trials and health research studies is a notable challenge. Unsuccessful efforts to recruit participants from traditionally underserved populations can limit who benefits from scientific discovery, thus perpetuating inequities in health outcomes and access to care. In this study, we evaluated direct mail and email outreach campaigns designed to recruit women who gave birth in North Carolina for a statewide research study offering expanded newborn screening for a panel of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Unfortunately, the expected booster effect of wave 2 mailing was not observed. Similar to the study by Paquin et al [ 37 ], sending booster mailers was ineffective. However, the cost-effectiveness analysis should be interpreted with caution since the mailers were not exclusively sent to eligible households.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Unfortunately, the expected booster effect of wave 2 mailing was not observed. Similar to the study by Paquin et al [ 37 ], sending booster mailers was ineffective. However, the cost-effectiveness analysis should be interpreted with caution since the mailers were not exclusively sent to eligible households.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, direct mailing proved to be a feasible, cost-effective and safe approach to inform eligible residents about the LHC grant, eligibility criteria and to motivate application for these funds during the pandemic. Direct mailing has been used to engage, interact with, and communicate public health information to assess public health information and/or encourage behavior change because of its relative ease, reach and equity [ [35] , [36] , [37] , [38] ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that a majority of women who received a my UNC Chart research invitation opened it, and of those who opened it, 4.88%, expressed in predicted probability, enrolled their newborn. In comparison, a previous analysis of the other primary recruitment method for Early Check, postnatal letters and emails to new mothers showed an overall statewide enrollment rate of 4% [ 36 ]. For those women who were sent a postnatal letter in addition to the recruitment invitation through my UNC Chart , the receipt of the postnatal letter did not increase the odds of enrollment.…”
Section: Discussionmentioning
confidence: 98%
“…We resumed social media advertising on Facebook and Instagram on April 1, 2020. An evaluation of the direct mail outreach impact on study enrollment showed that approximately 4% of all women who were sent a recruitment letter enrolled their newborn in the study, and the enrollment rate among women who also received a recruitment email was approximately 5% [ 36 ]. An analysis of the social media campaign from March 2019 to September 2019 showed that paid ads on social media resulted in 3.5 additional daily enrollments in the study for each day ads were run [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main considerations was how to best recruit families. [61][62][63] Barriers to full-scale newborn screening for FXS include public health burden to conduct the screening; the need for inexpensive, high-throughput screening methodologies; lack of demonstrated treatment for asymptomatic children; and insufficient capacity for long-term followup. 64,65 Health Care Needs and Access Indirect and direct health care costs are sizable for individuals with FXS.…”
Section: Public Health Needsmentioning
confidence: 99%